Statement of Removal (Communications in statistics. Simulation and computation, 2022)
This article has been removed from the online journal as it was a duplicate publication which was published in error. The publisher apologies for any confusion caused. Article title: Preface Authors: L. Cui & T. Dohi Journal: Communications in Statistics - Simulation and Computation Version of Record Published Online: 08 January 2014 DOI: http://dx.doi.org/10.1080/03610918.2013.875438